Research of antimicrobial properties of phytoextracts and their functionalizathion with carbonized rice husk (Experimental biology, 2015)
Was carried out research of antimicrobial properties of Salvia officinalis, Calendula officinalis L., Herba bidentis,Achillea millefolilius and their functionalizathion with carbonized rice husk referring to intestinal pathogens, food toxicinfections and purulent inflammation bacteria – Echerichia coli, Enterococcus sp., Staphylococcus aureus, Salmonellatyphimurium. Phytoextracts functionalizathion with carbonized rice husk relatively with phytoextracts showed highantimicrobial activity referring to the test cultures.
Keywords: phytoextract; carbonized rice husk; sorbent; antimicrobial properties; functionalizathion; herbal plants; toxic infections; purulent inflammation processes